The Two Crises of the Church - Van der Meulen, Marten; van den Berge-Bakker, Jonna (Ecclesial Futures, 2024)
In this article we examine the two crises of the Church: crisis 1, which is the decline of the Church, and crisis 2, which is the Church forgetting its calling. Crisis 1 draws the most attention from churches, but it is crisis 2 that churches should attend first. We argue that the order matters: a church paying attention to its calling will not solve its decline, but will help break free from tiresome attempts at repair. It will also help churches to practise an attitude of receiving, being directed at the kingdom of God. The distinction between crisis 1 and 2 will help churches and theologians name the challenges that the Church faces and will help prioritize them. It requires that discernment as a communal practice with others becomes an important part of the theological method.